2008
DOI: 10.1177/1028315308321994
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and the International Student Experience

Abstract: An implicit perception of international students is that they have difficulty in becoming involved in social exchange with other students who do not share their “culture” and language. This picture of a group of students isolated and disadvantaged by their lack of contact with “UK culture” is questioned in this article. Data from a recent research project suggests that international students form a strong international community that supports their learning and provides them with a supportive learning environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
167
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(182 citation statements)
references
References 6 publications
14
167
0
1
Order By: Relevance
“…Many scholars suggest that students learn in new ways using social media and that educators should embrace these new platforms (Jenkins, 2006). Furthermore, the higher-education sphere is also beginning to use the SNs (Gray et al, 2010;Montgomery & McDowell, 2009;Yang & Cheng, 2010). In classrooms, this resource is sometimes used to create specific academic groups, forums, spaces for debate or virtual communities of practice, all of which are coordinated by a teacher or tutor with specialized knowledge of the topic at hand.…”
Section: While This New Social and Communication Phenomenon Is The Momentioning
confidence: 99%
“…Many scholars suggest that students learn in new ways using social media and that educators should embrace these new platforms (Jenkins, 2006). Furthermore, the higher-education sphere is also beginning to use the SNs (Gray et al, 2010;Montgomery & McDowell, 2009;Yang & Cheng, 2010). In classrooms, this resource is sometimes used to create specific academic groups, forums, spaces for debate or virtual communities of practice, all of which are coordinated by a teacher or tutor with specialized knowledge of the topic at hand.…”
Section: While This New Social and Communication Phenomenon Is The Momentioning
confidence: 99%
“…Of particular concern is the paucity of intercultural interactions involving local students (Dunne, 2009;Harrison, 2012). While some research suggests that international students are engaging in intercultural interactions (Montgomery & McDowell, 2009), this typically involves other international students. By contrast, local students experiences of diversity on campus are tangential, with international and local student cohorts often studying and socialising in parallel (Kimmel & Volet, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While studies such as Montgomery andMcDowell (2009) andZappa-Hollman andDuff (2015) have identified classmates and other peers as a common source of academic peer support, these findings provide a more detailed understanding of different types of peers and their potential limitations. Peers in the same academic level were not typically more knowledgeable about academic matters than the seekers themselves.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Several studies have investigated the social dimension of international students' academic learning, suggesting the importance of peer relations (Che, 2013;Montgomery & McDowell, 2009;Nam & Beckett, 2011;Séror, 2011;Zappa-Hollman & Duff, 2015). Several studies, for example, highlight how peers were preferred over institutional advisors.…”
mentioning
confidence: 99%
See 1 more Smart Citation